Protein Methyltransferases - Clarke, Steven G.; Tamanoi, Fuyuhiko (Enzymes ;, 2006)
Protein methylation has recently emerged as one of the most exciting areas of study on posttranslational modification. A large family of protein methyltransferases has been identified and their structural properties have been characterized. These studies have provided novel insights into how methylation regulates a variety of biological functions including DNA and RNA metabolism, protein synthesis and signal transduction. Methylation also plays important roles in aging. This volume is intended to capture these recent developments concerning protein methyltransferases.